Microscopic and molecular epidemiology of gastrointestinal nematodes in dairy and beef cattle in Pak Chong district, Nakhon Ratchasima province, Thailand - Chompunoot Wangboon; Pongsakorn Martviset; Mantana Jamklang; Sirilak Chumkiew; Watsana Penkhrue; Sainamthip Rangdist; Ruttiroj Jirojwong; Wansika Phadungsil; Pathanin Chantree; Rudi Grams; Dawid Krenc; Pantip Piyatadsananon; et al. (Veterinary World, 2024)
Background and Aim: Gastrointestinal (GI) nematode infection remains an important problem in livestock, particularly cattle. The infection may lead to serious health complications and affect animal products. The objective of this study was to investigate GI nematode infection and its associated risk factors in dairy and beef cattle farmed in Pak Chong District of Nakhon Ratchasima Province, northeast Thailand.